The whole of university experience : retention, attrition, learning and personal support interventions during undergraduate business studies : final report 2011. - Willcoxson, Lesley; Manning, Mark; Wynder, Monte; Hibbins, Ray; Joy, Sally; Thomas, Jan; Girardi, Antonia; Leask, Betty; Sidoryn, Tristana; Cotter, Julie; Kavanagh, Marie; Troedson, David; et al. (Australian Learning and Teaching Council (ALTC), 2011)
This paper examined factors underpinning attrition in the first, second and third year of a business degree at six Australian universities Griffith University, Monash University, Murdoch University, University of South Australia, University of Southern Queensland, and University of the Sunshine Coast. It enabled gathering of data relating to demographics; students experience of university; their use and perceptions of the usefulness of student support interventions; open-ended comments about the best and worst aspects of the university experience; and aspects in need of improvement. In each year a small number of students were also interviewed for the purpose of fleshing out the survey data and exploring the interactions between various factors associated with attrition. Overall, the data strongly indicates that factors related to attrition are generally university-specific and reflect both student characteristics and their responses to the specific institutional culture and environment. The only attrition triggers which span most universities and most years of study are lack of a clear reason for being at university and the feeling of having insufficient ability to succeed at university. Practically, the project has delivered, and will continue to deliver, significant value to the higher education sector. On the basis of evidence from the project, partner universities have begun addressing high-value student retention issues and it is expected that this evidence will continue to influence institutional decision-making for several years beyond the life of the project. Dissemination activities external to partner universities, including publication of five journal articles and numerous workshops or presentations, have assisted staff in other universities to reflect upon issues critical to student retention in both first year and beyond. [Executive Summary, ed]